Arabic Language Learning Methods In The Digital Era - Nafilah, Sayidah Alfa; Hamidi, Saddam Reza; Maulidiyah, Robi'atul Laili; Faruq, Muhammad; Mufidah, Nuril (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aims to describe the role of digital learning in Arabic and explain how effective methods are in learning Arabic in the digital era. This is qualitative descriptive research. Data was collected by observation and interviews with students of the 2023 Arabic language development special program at UIN Malang, Indonesia, about the learning methods used. The research results are that the currently developing digital era can make it easier for students to learn by using technology as a learning medium. A practical method of learning Arabic is getting used to answering online exercises to practice reading, writing, and speaking so that one can master learning Arabic. Apart from that, the current problem is that technology also hurts young people because of their dependence on cell phones, which can also be used as entertainment.